Assessment of diversity and cultural importance of wild Plants in district Sargodha, Punjab, Pakistan - Aziz, Abida; Abbas, Qamar; Azhar, Muhammad Farooq; Ali, Ehsan; Perveen, Shazia; Hafiz Bashir Ahmad; Muhammad Sajjad Haider; Muhammad Talha Imtiaz (Ethnobotany Research and Applications, 2024)
Background: The present study was conducted in the town of Miani, district Sargodha, Punjab to make an inventory of economically important plants and further assess their conservational status by documenting the indigenous knowledge of local communities, hakims, and plant experts. The locals have close contact with the neighboring plant resources. Methods: Quadrat and line transect methods were used for vegetation sampling. Several parameters like plant availability, exploitation level, and conservation efforts were studied. After the primary survey, 19 important medicinal wild plants of the area were short-listed with the help of local inhabitants and hakims. 100 samples were collected from 4 sites Results: The most abundant species were Artemisia absinthium and Cannabis sativa. The cultural importance and conservational status of economic and medicinal plants in the area were also assessed. Major species of the study area belong to the family Asteraceae (19.05%). Artemisia absinthium has a higher plant density (0.12). Cannabis sativa has the highest significance factor and Chenopodium album has the 2nd highest value of the Cultural Significance Index (CSI) in the study area. Cannabis sativa has the highest significance factor and Chenopodium album has the 2nd highest value of CSI in the study area. Conclusions: It is concluded that the area offers a high potential for plant resources and a rich tradition of indigenous knowledge about how to utilize these species but the economic potential should be channelized and explored because these species are usually treated as wild weeds. Keywords: Wild Medicinal plants, Conservation, Economic importance, Cultural Significance Index (CSI), plant resources.